2013
DOI: 10.3389/fpls.2013.00281
|View full text |Cite
|
Sign up to set email alerts
|

Control of Zn uptake in Arabidopsis halleri: a balance between Zn and Fe

Abstract: Zinc (Zn) is an essential plant micronutrient but is toxic in excess. To cope with excess Zn, plant species possess a strict metal homeostasis mechanism. The Zn hyperaccumulator Arabidopsis halleri has developed various adaptive mechanisms involving uptake, chelation, translocation and sequestration of Zn. In this mini review, we broadly discuss the different Zn tolerance mechanisms and then focus on controlled Zn uptake in A. halleri. Members of the ZRT/IRT-like protein (ZIP) family of metal transporters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 58 publications
4
34
0
1
Order By: Relevance
“…B). These results indicated that Fe and Zn concentrations in Arabidopsis shoots inversely change by the concentration of any one of these two nutrients, which is similar to previous reports . Moreover, the concentrations of Mn, Co, Mo, and Cu showed similar varying tendencies to Zn, namely their concentrations were increased by Fe deficiency (Supporting Information Table 1).…”
supporting
confidence: 90%
“…B). These results indicated that Fe and Zn concentrations in Arabidopsis shoots inversely change by the concentration of any one of these two nutrients, which is similar to previous reports . Moreover, the concentrations of Mn, Co, Mo, and Cu showed similar varying tendencies to Zn, namely their concentrations were increased by Fe deficiency (Supporting Information Table 1).…”
supporting
confidence: 90%
“…In A. thaliana , it is well documented that Zn excess results in a secondary Fe deficiency response (Wang et al ., ; Shanmugam et al ., , ). Comparative studies of A. halleri ssp .…”
Section: Discussionmentioning
confidence: 99%
“…The results presented for plants from populations B and W suggest an increase of the Fe accumulation in the shoots with an increasing accumulation of Zn and Cd in the shoots (Table II). A possible mechanism of the interaction between Zn and Fe, which prevents the toxic effect of Zn, was proposed by Shanmugam et al (2013). Recent reports also confirmed an increase in the accumulation of iron in the leaves of plants characterized by a hyperaccumulation of Zn and Cd (Stein et al, 2017).…”
Section: Parametersmentioning
confidence: 94%